Strategi Komunikasi Humas Bank Indonesia Dalam Sosialisasi Penerapan Transaksi Non Tunai (QRIS) Di Provinsi Bali - Swaryputri, I Gusti Agung Laksmi; Wibisono, Arief (Jurnal Kajian Ilmu Komunikasi, 2022)
An institution or organization should be able to establish good relations with the public. To develop good relations with the public, an organization must select a division or section of Public Relations (Humas). This research is entitled Bank Indonesia Public Relations Communication Strategy in Disseminating the Application of Non-Cash Transactions (QRIS) in Bali Province with the formulation of the problem of how the public relations communication strategy implemented by Bank Indonesia Bali Province in socializing the implementation of QRIS in Bali Province and the inhibiting and supporting factors in mixing the performance of QRIS as well as what benefits are obtainable when the community and government use QRIS in the Province of Bali. This study aims to determine the communication strategy of Bank Indonesia's public relations in the socialization of the implementation of Non-Cash Transactions (QRIS) in the Province of Bali, to find out the inhibiting and supporting factors in the socialization of the performance of QRIS in the Province of Bali. The research method used is the descriptive method. The research design uses a case study in BI Public Relations. The data collection method uses observation, interviews, and documentation methods, and the data analysis method uses descriptive qualitative methods. From the research results or conclusions, the steps obtained to follow the nature of the communication strategy, namely as an instrument to shape and direct people's expectations of the policies pursued and the targets to be achieved. In addition, the communication strategy includes public relations strategies in general. The benefits obtained when the community and government use